Glyphosate Shapes a Dinoflagellate-Associated Bacterial Community While Supporting Algal Growth as Sole Phosphorus Source - Wang, Cong; Lin, Xin; Li, Ling; Lin, LingXiao; Lin, Senjie (Frontiers in Microbiology, 2017)
Glyphosate is a widely used herbicide that can potentially be a phosphorus source for phytoplankton and microbes when discharged into the coastal ocean. In contrast to bacteria, few eukaryotic phytoplankton species appear capable of directly utilizing glyphosate. In this study, we observed, after a long delay (>60 days), Prorocentrum donghaiense, a dinoflagellate known to cause major harmful algal blooms in the East China Sea, could grow in a medium with glyphosate as the sole phosphorous, P, source; suggesting that P. donghaiense growth was through bacterial mediation. To understand how the bacteria community might respond to glyphosate, we analyzed the 16S rRNA genes of the microbial community present in P. donghaiense cultures when grown under lower (36 µM) and higher (360 µM) glyphosate concentrations. Based on both Sanger and Illumina high throughput sequencing, we obtained more than 55,323 good-quality sequences, which were classified into six phyla. As the concentration of glyphosate rose, our results showed a significant increase in the phyla Proteobacteria and Firmicutes and a decrease in the phylum Bacteroidetes. Further qPCR (Quantitative PCR) analysis showed higher abundances of two specific phylotypes in the higher-glyphosate P. donghaiense cultures when compared to the lower-glyphosate and no-glyphosate cultures. Correspondingly, qPCR displayed the same trend for the abundance of a gammaproteobacterial type of phnJ, a gene encoding Alpha-D-ribose 1-methylphosphonate 5-phosphate C-P lyase, which is responsible for phosphonate degradation. In addition, Tax4Fun analysis based on our 16S rRNA gene sequences results in higher predicted abundances of phosphonate metabolizing genes in glyphosate-treated cultures. This study demonstrates that glyphosate could selectively promote the growth of particular groups of bacteria within an algal culture and in glyphosate enriched coastal waters, this interaction may potentially further facilitate the growth of alga.